A new heuristic approach to rotorcraft system identification - Lu, Linghai; Agarwal, Dheeraj; Padfield, Gareth D.; White, Mark D.; Cameron, Neil (Vertical Flight Society, 2022)
High-fidelity rotorcraft flight simulation relies on the availability of a quality flight model that further demands a good level of understanding of the complexities arising from aerodynamic couplings and interference effects. This paper explores rotorcraft flight dynamics in the low-speed regime where such complexities abound and presents a new heuristic approach in the time domain to aid identification of nonlinear dynamics and fidelity assessment. The approach identifies flight model parameters “additively,” based on their contribution to the local dynamic response of the system, in contrast with conventional approaches where parameter values are identified to minimize errors over a whole maneuver. In these early investigations, identified low-order, rigid-body, linear models show good comparison with flight-test data. The approach is extended to explore nonlinearities attributed to the so-called maneuver wake distortion and wake skew effects emerging in larger maneuvers. The results show a good correlation for the proposed nonlinear model structure, demonstrated by its capability to capture the time response and variations of the stability and control derivatives with response magnitude.